Mercury concentrations provide an indicator of marine foraging in coastal birds - Lesley H. Thorne (Elsevier, 2021)
The transfer of nutrients between marine and terrestrial systems has important ecological consequences, and animal movement is an important driver of nutrient transfer. Coastal birds forage in marine environments and breed in terrestrial habitats, and thus serve as vectors moving nutrients from the sea to the land. However, urbanization can influence the extent to which coastal birds forage in marine or terrestrial environments due to the availability of human subsidies. Establishing a reliable and straightforward indicator of marine foraging would be useful for assessing changes in the use of terrestrial vs. marine habitats in the face of urbanization and broader environmental change, and for understanding the flow of nutrients and energy between terrestrial and marine environments. Mercury (Hg) is a highly toxic heavy metal which bioaccumulates in marine food webs, and is a potential indicator of marine foraging. Methylmercury (MeHg), is present only in aquatic ecosystems and reaches elevated concentrations in the prey species of marine birds. Thus, high concentrations of MeHg would be expected for birds foraging in marine environments in comparison to those foraging on terrestrial sources. We hypothesized that the degree of marine foraging influences Hg uptake in coastal birds. To test this hypothesis, we combined GPS tracking data with measurements of Hg concentrations in the blood of herring gulls (Larus argentatus) along an urban gradient in the northeast United States. We examined Hg concentrations for 51 individual herring gulls tracked with GPS tags at study sites representing high, medium and low degrees of urbanization. Our results showed a strong and significant positive relationship between Hg concentrations and the proportion of herring gull foraging locations occurring in offshore waters. Hg concentrations differed significantly between herring gulls whose primary foraging habitat occurred in marine vs. terrestrial environments. Gulls in more urban colonies spent less time foraging in marine environments, and had significantly lower Hg concentrations than those at the more remote study. Our results suggest that Hg concentrations in blood can be used to reflect the extent of marine foraging for animals using both marine and terrestrial habitats. Hg concentrations could be valuable monitoring tool to assess how the use of marine foraging habitats changes through time (dietary shifts) or relative to environmental change such as urbanization.